Intraoperative Floppy Iris Syndrome in patients on alpha 1 blocker tamsulosin: incidence and predictability - Srivastava, Anil K.; Gupta, Alka (International Journal of Research in Medical Sciences, 2020)
Background: Intraoperative Floppy Iris Syndrome (IFIS) was first described by Chang and Campbell in year 2005 in male patients undergoing phacoemulsification surgery who were on Tamsulosin, an alpha 1 blocker drug for their urinary symptoms for enlarged prostate. This condition was characterized by excessive floppiness of iris, prolapse of iris tissue through phaco and sideport incisions and progressive intraoperative miosis, resulting in increased surgical time and various major surgical complications compromising visual outcome. Methods: This study of 78 patients was undertaken to know the incidence and severity of IFIS as well as to predict its occurrence by observing maximum pupil dilation achieved preoperatively. Results: It was observed that majority of patients on tamsulosin dilated poorly and severe IFIS occurred in those with pupil dilation of 5 mm or less after putting mydriatic eye drops preoperatively. Conclusions: It was concluded that if IFIS was predicted and necessary precautions taken, postoperative complications can be reduced significantly with improved visual outcome.